PERBANDINGAN ALIRAN POSITIVISME DAN PASCAPOSITIVISME DALAM PARADIGMA PENELITIAN - Zulianti, Hajjah (Lentera: Jurnal Ilmiah Kependidikan, 2013)
This scientific writing entitle a contrastive study of positivism and pascapositivism in research paradigm is aimed to describe the positivism inpositivism era, to describe the criticize towards the positivism, to describe pascapositivism in pascapositivism era, and the differences betweenpositivism and pascapositivism in research paradigm. Based on the difference characteristics between positivism and pascapositivism, this scientific writing gives the benefit for the researcher to understand deeply about the characteristics of qualitative research which is very different from the quantitative. An understanding of this paradigm will lead the researcher to understand the characteristic of a research and use suitable approach inconducting a research.